2016
DOI: 10.1016/j.athoracsur.2016.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Success for the Convergent Atrial Fibrillation Procedure: 4-Year Outcomes

Abstract: Four-year outcomes for the convergent procedure are promising and demonstrate the ability to maintain sinus rhythm in a predominantly persistent and longstanding atrial fibrillation population. Increasing the extent of posterior ablation should be evaluated for patients with enlarged atria to account for the potential increase in fibrosis distribution and other atrial remodeling markers that produce arrhythmogenic substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 15 publications
(23 reference statements)
3
45
0
Order By: Relevance
“…In our study, we observed complication rate of 12.5% in the CVP group. A comparable complication rate was previously reported for a similar minimally invasive procedure used for treatment of persistent AF in a single‐center and multicenter study . CVP could be a safer option when compared to more invasive surgical approaches to paroxysmal AF treatment and more effective when compared to CA.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In our study, we observed complication rate of 12.5% in the CVP group. A comparable complication rate was previously reported for a similar minimally invasive procedure used for treatment of persistent AF in a single‐center and multicenter study . CVP could be a safer option when compared to more invasive surgical approaches to paroxysmal AF treatment and more effective when compared to CA.…”
Section: Discussionsupporting
confidence: 71%
“…Some data exist supporting ablation of the embryologically similar PV antra and LA posterior wall as a continuity in the treatment of AF . Moreover, the epicardial lesion pattern utilized in this study has also shown good long‐term outcomes in a mostly persistent AF patient population with 31% and 36% recurrence rates (cutoff of 1% AF burden) after 1 and 4 years of ILR monitoring …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Freedom from arrhythmia at 6 and 12 months post-procedure was 78.3% and 84.1%, respectively. Geršak et al reported similar success with convergent procedure for treatment in 76 patients with paroxysmal and non-paroxysmal AF and at 4 years follow up, 81% of patients were in sinus rhythm (86,87). Potential benefits of convergent procedure include less radiation exposure, shorter electrophysiology catheterbased procedure, reduction in the likelihood of esophageal injury that may be caused by endocardial ablation.…”
Section: Hybrid Approachmentioning
confidence: 66%
“…The well‐established use of catheter ablation in the treatment of AF as a safe and effective alternative to pharmaceutical therapy nevertheless appears to have reached an upper limit of long‐term success. Long‐term outcomes after AF ablation remain 40%‐65% successful after single procedure . The cause for procedure failure when no pulmonary vein reconnection occurs has prompted multiple hypotheses to explain continued AF occurrence.…”
Section: Discussionmentioning
confidence: 99%